Pengaruh Struktur Organisasi Dan Kepemimpinan Terhadap Kemampuan Sumber Daya Manusia Dan Dampaknya Terhadap Efektivitas Pelayanan Pendidikan Dasar Pada Dinas Pendidikan Kabupaten Bangkalan, Provinsi Jawa Timur - Bambang Budi Mustika (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2014)
Abstract: Indicator of the success of educational services, is when the ability and effectiveness of human resource services and the Department of Education as an agency officials education managers are already well underway, and the availability of sufficient reliable infrastructure and the allocation of funds in the business of giving satisfaction to the public through the provision of educational services, in accordance purpose of existence Government institutions as an public organizations.The research population was all state elementary school teacher Headmaster at Bangkalan Madura in East Java, as many as 666 people, with the criteria of the respondents are: 1). Headmaster of state elementary school teacher at Bangkalan Madura in East Java. 2). Headmaster of state elementary school teacher which already served 1 year minimum.From the test results of the models in this study, the Generalized Least Square Estimation (GLS), analysis of the Structural Equation Model (SEM), proportional random sampling method and software assistance Amos 20, on 247 respondents, able to explain the influence of organizational structure, leadership, and human resources for effective service in the Department of Basic Education at Bangkalan Madura in East Java.The results showed that: 1). Organizational structure can significantly affect the ability of human resource. 2). Organizational structure does not significantly affect the effectiveness of services. 3). Leadership significantly affect the ability of human resource. 4). Leadership significantly influences the effectiveness of the service. 5). Human resource capabilities can significantly affect the effectiveness of services. The results also show that the effectiveness of the service is not due to the direct influence of the organizational structure, but due to an indirect effect through the organizational structure of human resource capabilitiesKeywords: Organizational structure, Leadership, Human resource capabilities, Effectiveness of service